2008
DOI: 10.1128/cmr.00012-08
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models ofStreptococcus pneumoniaeDisease

Abstract: SUMMARY Streptococcus pneumoniae is a colonizer of human nasopharynx, but it is also an important pathogen responsible for high morbidity, high mortality, numerous disabilities, and high health costs throughout the world. Major diseases caused by S. pneumoniae are otitis media, pneumonia, sepsis, and meningitis. Despite the availability of antibiotics and vaccines, pneumococcal infections still have high mortality rates, especially in risk groups. For this reason, there is an exceptionally ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
108
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(114 citation statements)
references
References 272 publications
(345 reference statements)
2
108
0
4
Order By: Relevance
“…However, the utilization of monoclonal antibody-inactivated F. tularensis targets multiple Fc␥R types, including Fc␥RIIB, an inhibitory Fc␥R which negatively regulates the immune response when engaged (23), including by limiting production of antibody and protection against S. pneumoniae infection (12,17,24). Antibody plays a critical role in the prevention of pneumococcal disease through neutralization of virulence factors such as PspA and clearance of infecting pneumococcal organisms through opsonophagocytosis (16). Therefore, we sought to generate and test a vaccine that targets the protective immunogen, PspA, to a specific human activating Fc␥R, hFc␥RI, thereby bypassing interactions with Fc␥RIIB, while at the same time targeting a human Fc␥R in a unique hFc␥RI Tg mouse model.…”
Section: Figmentioning
confidence: 99%
“…However, the utilization of monoclonal antibody-inactivated F. tularensis targets multiple Fc␥R types, including Fc␥RIIB, an inhibitory Fc␥R which negatively regulates the immune response when engaged (23), including by limiting production of antibody and protection against S. pneumoniae infection (12,17,24). Antibody plays a critical role in the prevention of pneumococcal disease through neutralization of virulence factors such as PspA and clearance of infecting pneumococcal organisms through opsonophagocytosis (16). Therefore, we sought to generate and test a vaccine that targets the protective immunogen, PspA, to a specific human activating Fc␥R, hFc␥RI, thereby bypassing interactions with Fc␥RIIB, while at the same time targeting a human Fc␥R in a unique hFc␥RI Tg mouse model.…”
Section: Figmentioning
confidence: 99%
“…Even though the introduction of the polyvalent pneumococcal conjugate vaccines (PCV) has reduced the incidence of childhood carriage and disease for the vaccine serotypes (3-5), 1.6 million people die from pneumococcal infections annually, with the majority being children under the age of 5 (6). The development of pneumococcal disease depends on both bacterial factors, such as the pneumococcal capsular type or serotype, and the host innate immune response (7,8). S. pneumoniae expresses a plethora of virulence factors, of which the encapsulating polysaccharide layer is the most important and best studied so far (9, 10).…”
mentioning
confidence: 99%
“…The capsule confers antiphagocytic and antiopsonophagocytic properties that determine the invasive pneumococcal disease (IPD) potential of different serotypes (11). IPD is defined as the recovery of S. pneumoniae from a normally sterile site such as the blood or brain (7,12,13). To date, 97 distinct serotypes have been described based on the unique chemical and immunogenic properties of their capsule (10,14), and these serotypes can be divided into invasive as well as noninvasive/carrier serotypes (15, 16).…”
mentioning
confidence: 99%
“…21 To investigate whether this peptide has potential for use as an antibacterial agent against the difficult-to-kill Kp infection in clinics, the efficacy of IK8L against Kp-induced acute pneumonia and its role in the host defense were studied using our well-established mouse model. 46 Our data demonstrated that IK8L significantly alleviated severe infection after lethal dose challenge in mice, leading to significantly reduced bacterial burdens in major organs, decreased mortality, and lowered inflammatory cytokine response. Furthermore, these studies suggest that IK8L may be able to eradicate the invading bacteria, thereby attenuating inflammatory responses and avoiding tissue injury.…”
Section: Discussionmentioning
confidence: 53%